2021
DOI: 10.1055/s-0041-1731852
|View full text |Cite
|
Sign up to set email alerts
|

Oral Health Knowledge, Attitude, and Behavior of Nursing and Technical Students in Croatia

Abstract: Objective The aim of this study is to test knowledge, attitudes, and behavior of the students from the Bjelovar University of Applied Sciences in relation to oral health, and to determine the respectable differences between students of nursing and technical study programs. Participants and Methods Students were randomly selected to represent a convenient sample. A total of 140 students from nursing and technical studies were interviewed by using the World health organization Oral Health Questionnaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
1
0
0
Order By: Relevance
“…A survey of the student population in Zagreb showed that 83% of students brush their teeth two to three times a day, and 17% said they brush their teeth more than three times a day, all of whom were students at the Faculty of Dentistry [ 20 ]. A similar statement was made by students from Bjelovar, Croatia [ 21 ].…”
Section: Discussionsupporting
confidence: 59%
“…A survey of the student population in Zagreb showed that 83% of students brush their teeth two to three times a day, and 17% said they brush their teeth more than three times a day, all of whom were students at the Faculty of Dentistry [ 20 ]. A similar statement was made by students from Bjelovar, Croatia [ 21 ].…”
Section: Discussionsupporting
confidence: 59%